Bile salt and non-bile salt components in bile affecting micellar cholesterol uptake by rat intestine in vitro - Rampone, Alfred J. (1972)
1. The uptake of micellar cholesterol was measured in sacs of the upper half of everted rat intestine. Sacs of 20 cm length were incubated 1 hr in 25 ml. phosphate buffer containing fatty acid, monoglyceride and (3)H-labelled cholesterol in micellar form with the bile salt, sodium taurocholate, as the dispersing agent. 2. Sacs obtained from bile fistula rats (bile duct cannulated 48 hr previously) took up more than twice as much cholesterol as did sacs obtained from untreated control rats. 3. In experiments utilizing bile-deficient sacs increasing the sodium taurocholate concentration caused an increase in cholesterol uptake. Conversely, adding a small amount of whole bile caused a decrease in cholesterol uptake. 4. The inhibitory effects of the bile were greatly enhanced if the bile was pre-treated with cholestyramine to remove the bile salts. 5. It is concluded that bile has a variable effect on intestinal cholesterol absorption depending upon its relative concentration of bile salt and a non-bile salt component having opposite actions. 6. It is suggested that the variable effect may be related to the physico-chemical dispersion of cholesterol and that the non-bile salt component may be lecithin.